Capital humano e desenvolvimento econômico: um estudo de mercados emergentes e economias em desenvolvimento, com ênfase no Brasil - Souza, Évelyn Santos de (Universidade do Vale do Rio dos Sinos, 2024)
Human capital is a determinant factor for growth and economic development and for the competitiveness of national companies in the international market. Thus, the objective of this study is to analyze the relationship between human capital and economic development in emerging markets and in developing economies, with emphasis on Brazil. For this analysis, two indices directly related to the study subject were addressed, which are the Human Capital Index (HCI), calculated by The World Bank, and The Global Human Capital Index (GHCI), calculated by The World Economic Forum. The analysis of the indices addressed in this study allowed the evaluation of human capital evolution in these countries, and especially in Brazil. It was possible to conclude that the challenges include high rates of functional illiteracy, educational performance below the average in relation to other emerging countries, and socioeconomic disparities. The COVID-19 pandemic has exacerbated these issues, particularly impacting the quality of education. The study suggests strategies, including improvement in the quality of education, development of skills relevant to work, promotion of equality in education, expansion and valorization of vocational education, and programs to insert young people into the job market. This will not only strengthen human capital, but also boost economic growth and prosperity in the country.
Keywords: Capital humano; Desenvolvimento econômico; Brasil; Economias emergentes; Economias em desenvolvimento; HCI; GHCI; Human capital; Economic development; Brazil; Emerging economies; Developing economies; ACCNPQ::Ciências Sociais Aplicadas::Economia